2007
DOI: 10.1016/j.ydbio.2007.08.011
|View full text |Cite
|
Sign up to set email alerts
|

The Friend of GATA protein U-shaped functions as a hematopoietic tumor suppressor in Drosophila

Abstract: Drosophila has emerged as an important model system to discover and analyze genes controlling hematopoiesis. One regulatory network known to control hemocyte differentiation is the Janus kinase (JAK)/Signal Transducer and Activator of Transcription (STAT) signal-transduction pathway. A constitutive activation mutation of the Janus kinase Hopscotch (hopscotch(Tumorous-lethal); hop(Tum-l)) results in a leukemia-like over-proliferation of hemocytes and copious differentiation of lamellocytes during larval stages.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
106
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(117 citation statements)
references
References 39 publications
11
106
0
Order By: Relevance
“…Akt1 04226 is a lacZ enhancer trap creating an Akt1 hypomorphic allele (42). eater-GFP (*30, II) and eater-Gal4 (*217D201, II) were from T. Tokusumi (University of Notre Dame, Notre Dame, IN) (15,21). Gli-Gal4 (18,22), from M. Stern (Rice University, Houston, TX), drives expression in perineurial glia (43,44).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Akt1 04226 is a lacZ enhancer trap creating an Akt1 hypomorphic allele (42). eater-GFP (*30, II) and eater-Gal4 (*217D201, II) were from T. Tokusumi (University of Notre Dame, Notre Dame, IN) (15,21). Gli-Gal4 (18,22), from M. Stern (Rice University, Houston, TX), drives expression in perineurial glia (43,44).…”
Section: Methodsmentioning
confidence: 99%
“…1 C and G). By expression of the plasmatocyte-specific marker eater-GFP, the attached cells were identified as plasmatocytes, a macrophage-like cell type normally circulating in the hemolymph (15) (Fig. 1 D and D′).…”
Section: Egh Mutants Exhibit Enlargement Of Peripheral Nerves With Atmentioning
confidence: 99%
“…The ush gene belong to FOG family, the current studies found that all the FOG members function depends on the GATA transcription factors [3]. The ush can also interact with the srp to mediate the insect hemocytes differentiation [14,15]. In this study, we found that the ush gene not only express during molting and metamorphosis when hemocytes undergo differentiation, but the ush gene also express during feed stage.…”
Section: Discussionmentioning
confidence: 53%
“…Although the specific role of ush on larvae hemocytes differentiation is still unclear, but the knockdown of ush gene resulting in the destruction of drosophila hemocytes differentiation [15]. This results suggest that ush play an important role in larval hemocytes development.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation